Expressing a Target Mimic of miR156fhl-3p Enhances Rice Blast Disease Resistance Without Yield Penalty by Improving SPL14 Expression - Zhang, Ling-Li; Li, Yan; Zheng, Ya-Ping; Wang, He; Yang, Xuemei; Chen, Jin-Feng; Zhou, Shi-Xin; Wang, Liang-Fang; Li, Xu-Pu; Ma, Xiao-Chun; Zhao, Ji-Qun; Pu, Mei; et al. (Frontiers in Genetics, 2020)
MicroRNAs (miRNAs) play essential roles in the regulation of plant growth and defense responses. More and more, miRNA-3ps are reported to act in plant development and immunity. miR156 is a conserved miRNA, and most previous studies focus on its roles in plant growth, development, and yield determinacy. Here, we show that expressing a target mimic of miR156fhl-3p led to enhanced rice blast disease resistance without a yield penalty. miR156fhl-3p was differentially responsive to Magnaporthe oryzae in susceptible and resistant accessions. Transgenic lines expressing a target mimic of miR156fhl-3p (MIM156-3p) exhibited enhanced rice blast disease resistance and increased expression of defense-related genes. MIM156-3p also enhanced the mRNA abundance of SPL14 and WRKY45 by down-regulating miR156-5p and pre-miR156. Moreover, MIM156-3p lines displayed a decreased number of second rachis branches per panicle but enlarged grains, leading to unchanged yield per plant. Consistently, overexpressing miR156h (OX156) led to enhanced susceptibility to M. oryzae and decreased the expression of SPL14 and WRKY45. Our results indicate that miR156fhl-3p mounts a regulatory role on miR156-5p, which subsequently regulates the expression of SPL14 and WRKY45 to improve rice blast disease resistance.